Retinal Postphotoreceptor Layers and Macular Electroretinogram in Retinitis Pigmentosa - I. V. Zolnikova (Oftalʹmologiâ, 2020)
Purpose: to assess the inner retinal layer’s changes of the central retina in comparison with bioelectrical activity of macula assessed by MERG and with thickness of photoreceptor retinal layers in patients with retinitis pigmentosa.Patients and methods: 10 patients (20 phakic eyes) with RP were examined. Mean age was 27.0 ± 18.5 years. Mean best corrected visual acuity was 0.38 ± 0.22. The fundus photography electrophysiological studies were performed besides standard ophthalmological examination. Maximal electroretinogram (ERG) or cone-rod response, ERG to 30 Hz flicker and macular ERG were registered with electroretinograph MBN (Russia). Images were acquired using the protocol of scanning Macula radial (12 lines 9 mm long, each radial image is the average out of 50 scans) with settings ultrafine with automatic segmentation of the retina and calculation thickness. Retinal segmentation with the following calculation of different retinal layers was performed on SD-OCT RS-3000 Advance (Nidek, Japan) with obtainment of the map with 6 mm in diameter in accordance with the Early Treatment Diabetic Retinopathy Study (ETDRS).Results. We revealed increased thickness of retinal nerve fiber layer (RNFL), decrease of thickness of ganglion cell layer (GCL) (p < 0,05) and normal (p > 0,05) inner nuclear layer (INL) thickness. These structural changes are associated with the decrease of bioelectric macula’s activity measured by MERG (decrease of α- and β-wave amplitude) and decrease the thickness of photoreceptor layers in all zones according to EDTRS.Conclusion. Increase of thickness RNFL, decrease of GCL’s thickness and normal INL in patients with RP is associated with decrease of thickness of photoreceptor layers in EDTRS zones and decrease of amplitude of MERG.